Trypanosoma brucei Lipophosphoglycan Induces the Formation of Neutrophil Extracellular Traps and Reactive Oxygen Species Burst via Toll-Like Receptor 2, Toll-Like Receptor 4, and c-Jun N-Terminal Kinase Activation - Zhang, Kai; Jiang, Ning; Sang, Xiaoyu; Feng, Ying; Chen, Ran; Chen, Qijun (Frontiers in Microbiology, 2021)
Trypanosoma brucei brucei is the causative agent of African animal trypanosomosis, which mainly parasitizes the blood of the host. Lipophosphoglycan (LPG), a polymer anchored to the surface of the parasites, activates the host immune response. In this study, we revealed that T. brucei LPG stimulated neutrophils to form neutrophil extracellular traps (NETs) and release the reactive oxygen species (ROS). We further analyzed the involvement of toll-like receptor 2 (TLR2) and toll-like receptor 4 (TLR4) and explored the activation of signaling pathway enzymes in response to LPG stimulation. During the stimulation of neutrophils by LPG, the blockade using anti-TLR2 and anti-TLR4 antibodies reduced the phosphorylation of c-Jun N-terminal kinase (JNK), the release of DNA from the NETs, and the burst of ROS. Moreover, the addition of JNK inhibitor and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase inhibitor exhibited similar effects. Our data suggest that T. brucei LPG activates the phosphorylation of JNK through TLR2 and TLR4 recognition, which causes the formation of NETs and the burst of ROS.